Essential Oils Downregulate Pro-Inflammatory Cytokines and Nitric Oxide-Mediated Oxidative Stress in Alloxan-Induced Diabetogenic Rats - E. ul Haq, Muhammad; Akash, Muhammad S.H.; Rehman, Kanwal; Mahmood, Malik H. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Introduction: Hyperglycemia is associated with an elevated level of reactive nitrogen species (RNS) that leads to nitrosative stress and exacerbates the progression of diabetic complications. Methods: Present study was aimed to evaluate the therapeutic effects of essential oils (EOs) on increased serum levels of nitric oxide (NO) in diabetogenic rats. Diabetogenic rats were treated with EOs separately and/or in combination at the dose of 100 mg/kg, orally for one month. Blood sampling was done at the 1st, 15th and 30th day of the treatment period to investigate the effect of treatment on biomarkers of diabetic complications. Results: In diabetogenic rats, serum levels of NO, malondialdehyde (MDA) and pro-inflammatory cytokines were significantly increased when compared with that of the control group. Whereas, diabetogenic rats treated with EOs decreased serum levels of NO, MDA and pro-inflammatory cytokines up to a significant extent when compared with that diabetogenic rats treated with the standard antidiabetic drug. Moreover, EOs also increased insulin sensitivity in peripheral tissues and insulin secretion from β-cells of pancreatic islets more efficiently when compared with that of diabetogenic rats. Additionally, it was also found that EOs improved lipid profile and normal functions of kidney and liver as compared to that of diabetogenic rats. Conclusion: Findings of this study indicate that EOs may reduce pro-inflammatory cytokine levels by modulating the expression of NO. EOs may also ameliorate the nitrosative stress and maintain glucose homeostasis that are major culprits of diabetic complications.
Keywords: Essential oils